France between the wars : gender and politics - Reynolds, Siân. (London ; New York : Routledge, 1996)
Sian Reynolds challenges the prevailing assumption that women had little influence or power in France during the interwar period. She combines extensive empirical research with revealing insights into France's political history and women's history.
Book Cover; Title; Contents; Acknowledgements; Abbreviations; INTRODUCTION: WRITING ABOUT INTER-WAR FRANCE: THE TEXTBOOK AS TEXT; DEMOGRAPHY AND ITS DISCONTENTS; FROM KINDERGARTEN TO YOUTH HOSTEL: GROWING UP BETWEEN THE WARS; 'A SLIP OF A GIRL CAN FLY IT': THE FALSE PROMISES OF AVIATION; WHAT DID PEOPLE DO ALL DAY? THE SEXUAL DIVISION OF LABOUR IN FRANCE BETWEEN THE WARS; FROM THE DEPRESSION TO THE STRIKES: OUVRIERS AND OUVRIRES; THE TRUCE BETWEEN THE SEXES? THE POLITICS OF SOCIAL INTERVENTION FROM THE GREAT WAR TO THE POPULAR FRONT.
Includes bibliographical references (pages 252-267) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Women -- Political activity -- France; France -- Politics and government -- 1914-1940.; Femmes -- Activité politique -- France; France -- Politique et gouvernement -- 1914-1940.; POLITICAL SCIENCE -- Government -- General; POLITICAL SCIENCE -- Government -- National; POLITICAL SCIENCE -- Reference; POLITICAL SCIENCE -- Essays; Politics and government; Women -- Political activity; France; 1914-1940